Statins and Colorectal Cancer – A Systematic Review - Dobrzycka, Małgorzata; Spychalski, Piotr; Łachiński, Andrzej J.; Kobiela, Paulina; Jędrusik, Piotr; Kobiela, Jarek (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objectives Statins act by inhibiting 3-hydroxy-3-methylglutaryl-coenzyme A reductase and are an important drug class in the treatment of lipid disorders. They lower cholesterol levels and modulate cardiovascular disease risk in both primary and secondary prevention. In addition, some studies have shown that statins may have an effect on colorectal cancer development and treatment. Our objective is to summarize published studies on the effect of statins on colorectal carcinogenesis.Methods A systematic review of the PubMed and Cochrane databases was performed to identify studies published between April 2010 and April 2018 that investigated the association between statin use and colorectal cancer incidence, mortality, and treatment.Results Overall, 126 articles were identified with our search strategy. Based on the eligibility criteria, 69 studies were excluded from the review process. In vitro and animal studies have shown a potential chemopreventive effect of statins and their efficacy in adjuvant therapy of colorectal cancer. The anticarcinogenic effect on cancer risk in human studies was heterogeneous. Some studies reported better overall and cancer specific survival rates in patients using statins before and during colorectal cancer treatment. Statins also show a potential role in chemoprevention of colorectal cancer in patients with inflammatory bowel disease.Conclusions Accumulating evidence suggests that statins may have a role in colorectal cancer prevention and treatment. Further studies are necessary to define the associations between individual statin characteristics, their doses and colorectal cancer.
Keywords: colorectal cancer; cancer risk; statins